Millennial‐Scale Instability in the Geomagnetic Field Prior to the Matuyama‐Brunhes Reversal. (30th March 2018) - Balbas, Andrea Marie; Koppers, Anthony A. P.; Clark, Peter U.; Coe, Robert S.; Reilly, Brendan T.; Stoner, Joseph S.; Konrad, Kevin
Abstract: Changes in the Earth's magnetic field have global significance that reach from the outer core extending out to the uppermost atmosphere. Paleomagnetic records derived from sedimentary and volcanic sequences provide important insights into the geodynamo processes that govern the largest geomagnetic changes (polarity reversals), but dating uncertainties have hindered progress in this understanding. Here, we report a paleomagnetic record from multiple lava flows on Tahiti that bracket the Matuyama‐Brunhes (M‐B) polarity reversal ∼771, 000 years ago. Our high‐precision 40 Ar/ 39 Ar ages constrain several rapid and short‐lived changes in field orientation up to 33, 000 years prior to the M‐B reversal. These changes are similar to ones identified in other less well‐dated lava flows in Maui, Chile, and La Palma that occurred during an extended period of reduced field strength recorded in sediments. We use a simple stochastic model to show that these rapid polarity changes are highly attenuated in sediment records with low sedimentation rates. This prolonged 33, 000 year period of reduced field strength and increased geomagnetic instability supports models that show frequent centennial‐to‐millennial‐scale polarity changes in the presence of a strongly weakened dipole field. Key Points: We provide 40 Ar/ 39 Ar age determinations for Tahitian lava flows bracketing the Matuyama‐Bruhnes reversal A ∼33 kyr period of magnetic field instability preceded the final reversal A stochastic model is presented that reconciles age constraints between lava flow and sediment archives